Global Trends in Research on Microplastic Contamination and River Water Quality: A Bibliometric Review - Nisa Nur Agistni Eriana; Nia Kania; Meitria Syahadatina Noor; Eko Suhartono; Herawati Herawati (Universitas Malahayati Lampung, 2024)
ABSTRACT This study aims to analyse global trends in research related to microplastic contamination and river water quality using a bibliometric approach. Microplastics have become one of the most pressing environmental issues in recent decades, mainly due to their significant impact on aquatic ecosystems and potential harm to human health. Along with the increasing attention to this issue, the scientific literature related to microplastics and river water quality has grown rapidly. However, a thorough understanding of the distribution of research, relationships between topics, as well as potential research gaps is still needed to direct future research more effectively. This study used a literature search method through the Publish or Perish app, with keywords including